Factors affecting the women's empowerment in disaster risk governance structure in Sri Lanka. (December 2020) - Hemachandra, Kinkini; Amaratunga, Dilanthi; Haigh, Richard
Abstract: Women have been disproportionately affected by natural hazards due to many reasons. Minimum representation of women in disaster decision-making has been identified as such reasons for their high vulnerabilities in disasters. Hence, women's empowerment in disaster decision-making has been proposed by researchers and many international frameworks as a strategy to address vulnerabilities. Because women's empowerment in disaster risk governance is expected to reduce their vulnerabilities and strengthen overall societal resilience to future hazards. However, limited evidence is available on how to achieve women's empowerment in disaster risk governance. Hence, this chapter aims to explore the challenges that prevent their empowerment in disaster risk governance structure as input for policy makers of Sri Lanka. Sri Lanka was selected due to its increasing risks for disasters and the status of women's empowerment within the risk governance structure. Using a semi-structured interview guideline, which was developed based on the literature review, nine semi-structured interviews were conducted with the experts in the field of the study. Interview data were analysed qualitatively to identify the challenges that limit women's empowerment in disaster risk governance structure in Sri Lanka. The identified challenges are presented in this paper with the suggestions made by experts as inputs for the policymaking process. Accordingly, twenty challenges were identified within five broad themes as legal, institutional, individual, social & cultural and nature of the job. Accordingly, three suggestions were presented to overcome the identified challenges to enhance women's empowerment in disaster risk governance structure in Sri Lanka.